DIACHRONIC AND SYNCHRONIC METHODS IN LANGUAGE LEARNING (ACCORDING TO F. SAUSSURE) - Mukhtorova Nozima Ilhomovna (TADQIQOTLAR.UZ, 2024)
Abstract: In this article the information is given about the main features and characteristics of diachronic and synchronic methods in language learning according to F. Saussure. The article also clarifies the benefits of using these methods in foreign language learning and teaching. And there are given some researches about diachronic and synchronic methods.